V. I. Samoilo in Russian Periodicals and the Cultural Life of Wilno (1920–1939) - Лавринец, Павел (Literatūra, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] A native of Belarus, publicist, critic and author of poetic texts, Vladimir Samoilo (1878–1941), is well-known as a teacher of Yanka Kupala and a popularizer of his poetry. He is also known as a correspondent of Alexander Blok and an author of works on his creations, as well as a prominent figure of the Belarusian national movement. However, his participation in the Russian periodical press and in the social and cultural life in Wilno is insufficiently investigated. The aim of this study is to fill this gap. Samoilo was the organizer of the evenings of the famous Russian writers Dmitry Merezhkovsky, Zinaida Gippius and Dmitry Filosofov in 1920. He participated in discussions about the works of the Russian philosopher Nikolai Berdyaev, organized by the literary-artistic section of the Wilno Russian Society in 1925. He was an elected member of the council of the religious-philosophical section of the Wilno Russian Society in 1927. Later, Samoilo became vice-chairman of the religious-philosophical section. Samoilo was the author of a long speech given in 1931 at the solemn assembly of the 50th anniversary of the death of Fyodor Dostoevsky. At the meetings of the religious-philosophical circle, Samoilo made reports on the Russian philosophers Ivan Kireevsky, Pyotr Chaadayev and others. The newspapers Vilenskoe Slovo, Vilenskaya Misl and Utro published Samoilo’s articles on the topics of domestic and international politics as well as economy. He was the editor and publisher of the newspaper Vilenskaya Rech, where he published articles about the works of Alexander Blok and Fyodor Dostoevsky, also commenting on the historiosophic concept of Marian Zdziechowski. He was involved in an argument with the newspaper Vilenskoe Utro. Samoilo’s cooperation with the newspaper Nashe Vremia was accompanied with a polemic with the Warsaw newspaper Za Svobodu! and its head, Dmitry Filosofov, regarding Alexander Blok’s poem The Twelve. The most important publications of Samoilo in the newspaper Nashe Vremia are devoted to the history of Russian literature and philosophy as well to the discussions that were had in the religious and philosophical circle of the Wilno Russian Society. An analysis of the collected information clarifies the existing knowledge about the activities and views of Samoilo in the Wilno period and complements the general picture of the life of the Russian minority in the Wilno region and in the interwar Poland as a whole. Despite his contradictions and conflicts with certain representatives of the Russian society in Wilno, Vladimir Samoilo was its active and influential participant. V. I. Samojlo Vilniaus rusų periodikoje ir kultūriniame gyvenime (1920–1939) Gimęs Baltarusijoje publicistas, kritikas, eiliuotų tekstų autorius Vladimiras Samojlo (1878–1941) gerai žinomas kaip Jankos Kupalos mokytojas ir jo poezijos populiarintojas. Jis taip pat žinomas kaip Aleksandro Bloko korespondentas ir darbų apie jo kūrybą autorius bei baltarusių tautinio judėjimo žymus veikėjas. Bet jo dalyvavimas Vilniaus periodinėje spaudoje rusų kalba ir rusų visuomeniniame bei kultūriniame gyvenime ištirtas nepakankamai. Tyrimo tikslas yra užpildyti šią spragą. Samojlo 1920 m. buvo garsiųjų rusų literatų vakarų Dmitrijaus Merežkovskio, Zinaidos Gippijus, Dmitrijaus Filolsofovo organizatorius, 1925 m. dalyvavo Vilniaus rusų draugijos Literatūrinės-artistinės sekcijos surengtose diskusijose apie rusų filosofo Nikolajaus Berdiajevo veikalus. 1927 m. jis buvo išrinktas į Vilniaus rusų draugijos Religinės-filosofinės sekcijos tarybą ir darė pranešimą pirmajame sekcijos susirinkime. Vėliau jis tapo Religinės-filosofinės sekcijos vice-pirmininku. Samojlo buvo didelio pranešimo iškilmingame posėdyje Fiodoro Dostojevskio 50-ies mirties metinių proga 1931 m. autorius. Religinio-filosofinio ratelio susirinkimuose Samojlo darė pranešimus apie rusų filosofus Ivaną Kirejevskį, Petrą Čaadajevą ir kitus. Samojlo publikavo dienraščiuose „Vilenskoje slovo“, „Vilenskaja mysl“, „Utro“ straipsnius vidinės ir tarptautinės politikos bei ekonomikos temomis. Jis buvo dienraščio „Vilenskaja reč“ redaktorius ir leidėjas. Čia jis paskelbė straipsnius apie Aleksandro Bloko ir Fiodoro Dostojevskio kūrybą bei Mariano Zdziechowskio istoriosofinę koncepciją. Su dienraščiu „Vilenskoe utro“ Samojlo konfliktavo. Jo bendradarbiavimą dienraštyje „Naše vremja“ lydėjo 1931 m. polemika su Varšuvos dienraščiu „Za svobodu!“ ir jo vadovu Dmitrijumi Filosofovu dėl Aleksando Bloko poemos „Dvylika“ interpretacijos. Svarbiausios Samojlos publikacijos dienraštyje „Naše vremja“ skirtos rusų literatūros ir filosofijos istorijai bei diskusijoms Vilniaus rusų draugijos Religinio-filosofinio ratelyje. Surinktų duomenų analizė patikslina turimas žinias apie Vilniaus laikotarpio Samojlos veiklą ir pažiūras bei papildo Vilniaus krašto rusų mažumos ir visos tarpukario Lenkijos gyvenimo bendrą vaizdą. Nepaisant prieštaravimų ir konfliktų su atskirais Vilniaus rusų visuomenės žymiais atstovais, Vladimiras Samojlo buvo veiklus ir įtakingais šios visuomenės veikėjas.